2005
DOI: 10.1158/0008-5472.can-05-1757
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin-10-Induced Signaling of GPR54 Negatively Regulates Chemotactic Responses Mediated by CXCR4: a Potential Mechanism for the Metastasis Suppressor Activity of Kisspeptins

Abstract: The product of the KiSS-1 gene is absent or expressed at low level in metastatic melanoma and breast cancer compared with their nonmetastatic counterparts. A polypeptide derived from the KiSS-1 product, designated kisspeptin-10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 32 publications
(37 reference statements)
3
65
0
5
Order By: Relevance
“…Kisspeptin receptor stimulation has been demonstrated to inhibit calcineurin activity (Stathatos et al, 2005), which could also contribute to metastasis suppression. The kisspeptin receptor pathway seems to have the ability to disrupt signaling via the chemokine receptor CXCR4, thus inhibiting the prometastatic activity arising from interaction with its ligand, stromal cell-derived factor 1 (Navenot et al, 2005). Kisspeptin has been reported to induce apoptosis in cells, although there are conflicting reports about the role apoptosis may play in the metastasis-suppressing actions of kisspeptin (Harms et al, 2003;Becker et al, 2005).…”
Section: Receptor Signalingmentioning
confidence: 99%
“…Kisspeptin receptor stimulation has been demonstrated to inhibit calcineurin activity (Stathatos et al, 2005), which could also contribute to metastasis suppression. The kisspeptin receptor pathway seems to have the ability to disrupt signaling via the chemokine receptor CXCR4, thus inhibiting the prometastatic activity arising from interaction with its ligand, stromal cell-derived factor 1 (Navenot et al, 2005). Kisspeptin has been reported to induce apoptosis in cells, although there are conflicting reports about the role apoptosis may play in the metastasis-suppressing actions of kisspeptin (Harms et al, 2003;Becker et al, 2005).…”
Section: Receptor Signalingmentioning
confidence: 99%
“…GPR54 activation by kisspeptins was shown to block chemotaxis to fetal bovine serum, activate extracellular signal-regulated kinase (ERK) mitogenactivated protein kinase, induce formation of stress fibers, phosphorylate focal adhesion complex, decrease expression of matrix metalloproteinase 9, and reduce cell proliferation in receptor transfectants (Kotani et al, 2001;Ohtaki et al, 2001;Yan et al, 2001). We have shown previously that activation of GPR54 by kisspeptin-10 (Kp-10) inhibited chemotaxis induced by stromal cell-derived factor 1/CXCL12 and its receptor CXCR4 (Navenot et al, 2005), a mechanism shown in several models to be involved in the migration of CXCR4ϩ tumor cells to the organs that secrete its ligand such as the lungs, liver, brain, and bones (Mü ller et al, 2001). Activation of GPR54 suppressed Akt phosphorylation by CXCR4 (Navenot et al, 2005).…”
mentioning
confidence: 99%
“…BRMS1 and CXCR4 are also inversely correlated in non-small cell lung cancer cases indicating that one mechanisms of BRMS1 suppression of metastasis is downregulation of CXCR4. KISS1, and protease cleavage-derived kisspeptins, prevent SDF-1 induced CXCR4 chemotaxis (41). While further studies will be required to establish definitive connections between CXCR4, KISS1/BRMS1 and metastasis suppression, the implications provide testable hypotheses regarding mechanisms of metastasis suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Both metastasis suppressors significantly reduce (or prohibit) tumor cell proliferation in ectopic sites (22,39). Intriguingly, BRMS1 and KISS1 both regulate CXCR4 signaling (40,41). In non-small cell lung cancer, BRMS1 reduces CXCR4 expression through inhibition of NFκB resulting in an inhibition of SDF-1 induced migration (40).…”
Section: Discussionmentioning
confidence: 99%